Designing a financial literacy development model for Farhangian University students - Mohsen Molapanah; Yousef Namvar; Azam Rastgoo; Majid Ahmadlu; Toran Soleimani (مدیریت و چشم انداز آموزش)
AbstractThe aim of the current research was to design a model for the development of financial literacy of Farhangian University students. The research method was mixed (qualitative-quantitative), and the research community in the qualitative part included professors, specialists and experts in the financial field; and in the quantitative part, it included all students of Farhangian universities in Ardabil province. In the qualitative section, 21 experts were selected by purposeful selection; and in the quantitative section, 278 students were selected using statistical formulas as a non-random sampling method. Research tools included semi-structured interviews and researcher-made questionnaires. The analysis of the data collected in the qualitative part was done using the grounded theory method using Maxqda 11 software; in the quantitative part using two methods: descriptive and inferential, using Smart PLS and spss22 software. The results showed that based on the three categories of knowledge, behavior and attitude in the discussion of financial knowledge gender, place of residence; the indicators of parents' education and place of residence were effective in the discussion of financial attitude, and in the field of financial behavior; permanent place of residence and student's income were determined as more effective factors in the financial literacy of Farhangian University students. Based on the extracted model, the knowledge component ranks first in terms of the impact on students' financial literacy with a factor load of 0.751, followed by the behavior component with a factor load of 0.730 and attitude with a factor load of 0.667.Extended abstractIntroductionIn this century, just reading and writing and even knowing a second language cannot indicate to be literate. According to the definition of Shirzadi (2018), a literate person is a person who has six types of literacy; educational, emotional, communication, media, computer, and financial; every person should have sufficient knowledge about financial affairs and take steps to strengthen their financial literacy (Rahmani & Mohammadi, 2019).What is certain is that the role of educational and school systems in the creation, growth and development of financial and economic literacy in today's societies becomes more and more important (Taftian, Azdi, & Rejal, 2018). Researches show that those who have received financial training in high school or at work can save businesses (Bernheim & Garrett, 2003). To solve this deficiency, centers have been established to teach financial literacy and financial management styles, all of which are trying to improve the level of financial literacy in the country. The most common of these centers, as all students pass through it, are schools. On the other hand, the educational institution and especially the teachers as one of the pillars and components of the educational institution, along with the family, are among the most influential factors of citizenship education. Therefore, this basic question is raised: how much do future teachers know about financial literacy and do they use it in the process of life? Therefore, in this research, the financial literacy development model of Farhangian University students is examined.methodologyThe current research was a mixed method (qualitative-quantitative), and three stages were passed to achieve the research questions according to the nature of the goals and research questions. In the first stage; the qualitative part, two steps were taken to answer the first question of the research, that is, to determine the components of financial literacy; in the first step, the theoretical foundations and the background of the research were examined using the document analysis method, and then the components of financial literacy were extracted and formulated. In the second step, based on the components identified in the first step, a semi-structured interview was conducted with experts and experienced experts in the financial field, and the data obtained from the semi-structured interview using Maxqda11 software were determined in the form of ground theory method, units Semantic coding, analysis and components of financial literacy.In the second stage of the qualitative part, the Delphi method was used to answer the second research question; therefore, the components determined in the first stage were provided to financial experts to determine the factors related to the financial literacy of Farhangian University students. After the agreement and approval of the experts, the indicators related to the financial literacy of Farhangian University students were selected to prepare the final questionnaire focusing on the components of financial knowledge, financial attitude and financial behavior. The qualitative research community was formed by professors, specialists and experts in the field of finance who had numerous articles and publications. The number of samples in the qualitative section, which were purposefully selected by the snowball method until reaching theoretical saturation, were 21 professors, specialists and experts in the field of finance.In the third stage, i.e. the quantitative part, confirmatory factor analysis and structural equation modeling were used to answer the third question of the research, i.e. the financial literacy model of Farhangian University students. The population of the quantitative part consisted of all the students of Farhangian universities in Ardabil province, and to determine the sample size, the structural equation modeling sampling formula (q ≤ n ≤ 15q5) was used, where q is the number of questions in the questionnaire and n is the desired sample size (Homan, 2013).. Based on the 29 questions of the questionnaire, a minimum of 145 and a maximum of 435 students were determined based on the sample size, and finally 278 questionnaires were collected using Cochran's formula. The research tool was a researcher-made questionnaire that was prepared using the data extracted from the qualitative method. The analysis of the collected data was done in the quantitative part by two descriptive and inferential methods using Smart PLS and spss22 software. In order to collect data, a researcher-made questionnaire with 29 questions based on a five-point Likert spectrum was used. The content validity ratio for the whole has been obtained as 0.892; therefore, according to experts, the questionnaire components and the entire questionnaire have good content and form validity. Confirmatory factor analysis method has been used to check the validity of the measurement model.Discussion and ResultsThe findings of the research regarding the first question of identifying the components of financial literacy revealed that various factors influence people's financial literacy, and other factors are involved and shifted according to the conditions of individuals from different angles. Coherent studies have not been conducted to identify the factors affecting people's financial literacy, and most of the researches have analyzed and investigated a specific axis of employment or positions. After expert review of articles and scientific sources and comparison of opinions and appeals' 13 factors (parents' education, family member's education in financial field, area of residence, family's financial knowledge, social class, individual's income, housing situation, individual's level of education, individual's family background, marital status, number of dependents, age) were identified as the most important factors affecting the financial literacy of Farhangian University students. By examining the theoretical foundations, empirical studies regarding the second question of the research based on the factors that are most related to the financial literacy of student teachers have been taken into consideration. Research shows that the most effective criteria are family financial awareness, individual financial awareness, parents' education, family member's financial education, individual's education level, individual's income, and social class in the field of financial literacy of Farhangian University students, among which, by Delphi method implementation, 7 agents were confirmed. The findings of the research regarding the third research question about the financial literacy model of Farhangian University students showed that in the conceptual model of the research, all three components of knowledge, attitude and behavior were effective on the financial literacy of Farhangian University students and based on the extracted model, the knowledge component in terms of amount influence on students' financial literacy is in the first rank, and the behavior and attitude component are in the next ranks. Confirmatory factor analysis shows that the model has good reliability. The study is based on the observed criterion of the goodness index of the appropriate power of the model in the prediction of the appropriate endogenous variable. According to the coefficient of determination, the structural model under investigation is of appropriate quality. The findings of this research are in agreement with the findings of Ojand & Mahmoudpour (2023), Jana, Sinha, & Gupta (2024), Kazempour Dizji et al., (2020), Moeinfar et al., (2023), Purwidianti et al., (2022), Novitasari et al., (2021), Baker et al., (2018), and Taftian & Tajamlian (2020).ConclusionAccording to the results obtained for improving the level of financial literacy in the society, which definitely has many effects on the level of welfare of the society and increasing production, regarding the knowledge level of the development of public education and providing reasons for increasing the level of financial literacy in the field of basic concepts such as the government's guarantee for deposits in banks, the current value of investments and specific financial knowledge questions such as credit card, interest compounding, time value of money, the effect of inflation on the price level and investment must be provided, which in addition to responding to cultural and social needs, can be the basis for the growth and progress of the society that seeks development. At this level, depending on the necessity of financial literacy education and its impact on the country's economy, it is necessary to develop a curriculum for different educational levels and also design financial literacy education courses for different sections of the society. In this context, the awareness of the society can be increased by holding educational workshops and seminars, holding medium-term and long-term training courses.Using magazines, brochures and books, extensive culture building through the national media is worthy of attention to improve the attitude level of the society. This important issue in Iran and especially in the capital market has been pursued by various institutions, including the stock Exchange Organization, Tehran Stock Exchange, Exchange Information and Services Company and other public and private institutions; but measures should be taken in such a way that the individual's reaction to factors such as inflation, exchange rate, risk and financial planning is reasonable and correct. At the level of financial behavior, by providing the conditions for the use and implementation of the knowledge and mindsets of the people of the society through the transfer of shares and the permission to buy and sell, etc., which will reduce the risk-taking of people, so that before making a decision on investment, all financial products should carefully and thoughtfully evaluated, save instead of borrowing, do his own assessment of the affordability of products and services, and plan for retirement.Curriculum planners, who are the main custodians of curriculum development, using the results of this research and using the issues and general principles of financial literacy education; by developing a curriculum specific to financial literacy, should present the goals, content, method and evaluation in the form of two units of study in Farhangian University.In the current research, some limitations were effective; in the discussion of attitude measurement structure; that definite measurement is not possible. Another case is related to demographic asymmetry in Ardabil cultural universities, where the population of boys is more than girls; therefore, caution should be taken in generalizing the research and it is suggested to conduct a parallel research. The presented model is specific to Farhangian University with its own characteristics; Therefore, it is possible to generalize with other societies.